การจัดสมดุลสายการผลิตเพื่อเพิ่มผลผลิตในโรงงานเก้าอี้ทันตกรรม - นิสา ชัยนภาพร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This thesis has the main objectives to study and reduce production lost in the assembly line and part production activities of a dental chair company. From the study, it is revealed that problems in the manufacturing and dental chair assembly lines are in terms of waiting and delays. The unbalancing production lines are generated by the problems of parts production scheduling and uneven assembly functions resulted in production delay. The production improvement of the dental plant started by the endeavor to balance the assembly line. By analyzing the subassembly lines, it is revealed that there exist problems of waiting for delayed parts while there are work-in-process materials in the form of parts waiting for assembly. The parts production controlling system is set by designing a new parts and works coding system related to the stages of assembly and made it possible to leveling all assembly parts to be ready for subassembly and assembly operations on time. By balancing the assembly operations and improving part production activities, the production is increased from 33 units/month to 48 units/month. The average number of late delivery is reduced from 1 units/month to 0.33 units/month. Work-in-process inventories and waiting time for parts arriving are minimized.